Use of Propensity Score Matching to Compare Short Outcomes from Transoral and External Surgical Approaches in Patients with Deep-Lobe Parotid Pleomorphic Adenomas - Yue Fan; Shuguang Li; Shuting Yu; Xiaoli Zhu; Xiaohua Shi; Wuyi Li; Zhiqiang Gao; Xingming Chen (Current Oncology, 2021)
To compare the outcomes of patients who had deep-lobe parotid gland pleomorphic adenomas (PAs) that extended into the parapharyngeal space after surgical treatment, using a transoral approach or an external approach. One hundred and twelve eligible patients, with deep-lobe parotid gland PAs, were enrolled in this retrospective study. The surgical outcomes were compared for patients who received a transoral approach and an external approach, using 1:1 propensity score matching (PSM). The outcome measures were recurrence rate, facial nerve deficit, Frey’s syndrome, and hospitalization time. The median follow-up time was 4.8 years. After PSM, the transoral approach and external approach groups had no statistically significant difference in recurrence (10.3% vs. 3.4%; p = 0.201). The transoral approach group had no facial nerve deficit, but 5 of 29 patients (17.2%) in the external approach group had transient facial nerve paralysis (p = 0.052). The external approach group had a longer hospitalization time than the transoral approach group (5 vs. 4 days, p = 0.0017). The use of a transoral surgical approach to treat patients with deep-lobe parotid gland PAs led to low recurrence, shorter hospitalization times, and good functional and cosmetic outcomes.